Cardiac Rehabilitation After Open Heart Surgery: A Narrative Systematic Review - Eleni Delimanoli; Olav Muurlink; Pavlos Myrianthefs; Anna Korompeli (Journal of Cardiovascular Development and Disease)
Background: Postoperative cardiac rehabilitation (CR) programs are increasingly recommended by clinicians, but only a minority of patients who have undergone open heart surgery participate in such programs. Participation rates in postoperative CR, if anything, appear to be declining. This systematic review examines the effectiveness of post-operative CR and reveals possible participation barriers. Methods: A search of two scholarly databases for primary research papers published in the last decade examining the impact of post-operative CR was conducted and the resultant papers reviewed. Results: The 21 resulting studies revealed physiological functioning improvement and a reduction in mortality and readmission rates, while highlighting an enhancement in mental status. Some of the studies recognized the need for nutritional support and suggested that age, gender, access to CR centers, and socioeconomic variables impact participation in CR. Conclusions: Post-operative CR participation rates continue to decline despite increasing evidence of the value of the approach.